Review of Aulacidae from Greece and Cyprus with new records - Turrisi, Giuseppe Fabrizio (ENTOMOLOGIA HELLENICA, 2013)
The Aulacidae (Hymenoptera: Evanioidea) from Greece and Cyprus are reviewed. Seven species are recorded, all comprised within the genus Pristaulacus Kieffer, 1900. Two of them, P. chlapowskii Kieffer, 1900 and P. compressus (Spinola, 1808) are reported for the first time from Greece; P. mourguesi Maneval, 1935, previously known from only one locality of northern Greece, is recorded for the first time from the Eastern Aegean islands (Ikaria) and other localities from the Greek mainland are reported; P. galitae (Gribodo, 1879) is recorded for the first time from Lesvos island (Eastern Aegean islands) and Cyprus. Brief references for identification and essential data on the treated species are provided.